Nutritional Status Evaluation in Patients Affected by Bethlem Myopathy and Ullrich Congenital Muscular Dystrophy - Toni, Silvia; Morandi, Riccardo; Busacchi, Marcello; Tardini, Lucia; Merlini, Luciano; Battistini, Nino Carlo; Pellegrini, Massimo (Frontiers in Aging Neuroscience, 2014)
Collagen VI mutations lead to disabling myopathies like Bethlem Myopathy (BM) and Ullrich Congenital Muscular Dystrophy (UCMD). We have investigated the nutritional and metabolic status of one UCMD and seven BM patients (5 female, 3 male, mean age 31 ± 9 years) in order to find a potential metabolic target for nutritional intervention. For this study, we used standard anthropometric tools, such as BMI evaluation and body circumference measurements. All results were compared to Dual Energy X ray Absorptiometry (DXA), considered the “gold standard” method. Energy intake of each patient was evaluated through longitudinal methods (7-day food diary) while Resting Energy Expenditure (REE) was predicted using specific equations and measured by indirect calorimetry. Clinical evaluation included general and nutritional blood and urine laboratory analyses and quantitative muscle strength measurement by hand-held dynamometry. BM and UCMD patients showed an altered body composition, characterized by low Free Fat Mass (FFM) and high Fat Mass (FM), allowing us to classify them as sarcopenic, and all but one as sarcopenic-obese. Another main result was the negative correlation between REE/FFM ratio (basal energy expenditure per kg of fat-free mass) and the severity of the disease, as defined by the muscle megascore (Correlation Coefficient -0.955, P value < 0.001). We postulate that the increase of the REE/FFM ratio in relation to the severity of the disease may be due to an altered and pathophysiological loss of energetic efficiency at the expense of skeletal muscle. We show that a specific metabolic disequilibrium is related to the severity of the disease, which may represent a target for a nutritional intervention in these patients.